2013
DOI: 10.7745/kjssf.2013.46.6.510
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Soil Loss According to Surface Covering and Tillage Methods in Corn Cultivation

Abstract: Corn was mainly cultivated in slope land during summer season when heavy rain falls so that soil loss occurs severely. Especially, soil disturbance and exposure of topsoil by conventional tillage intensifies soil loss by heavy rain. The aim of this study was to develop surface covering and tillage methods for reducing soil loss in corn cultivation. The experiment was conducted in 17% sloped lysimeter with 8 treatments including strip tillage after surface covering with rye residue, strip tillage after residue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2016
2016
2016
2016

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
1
0
1
Order By: Relevance
“…농경지의 토양 유실을 경감하기 위해 선진국에서는 무경 운 재배기술이 많이 연구되고 있는데, 특히 무경운 재배와 피 복작물을 결합하면 토양보전 효과가 매우 높은 것으로 밝혀 져 도입이 증가하는 추세이다 (Kim et al, 2004;Lee et al, 2013;Seo et al, 2005). …”
Section: ) ----------------(Kg Kgunclassified
“…농경지의 토양 유실을 경감하기 위해 선진국에서는 무경 운 재배기술이 많이 연구되고 있는데, 특히 무경운 재배와 피 복작물을 결합하면 토양보전 효과가 매우 높은 것으로 밝혀 져 도입이 증가하는 추세이다 (Kim et al, 2004;Lee et al, 2013;Seo et al, 2005). …”
Section: ) ----------------(Kg Kgunclassified
“…However, research have shown that just a 40-60% groundcover is sufficient to enhance returns for producers and support ecosystem health (Lee et al, 2014;Dobbratz, 2017). Ideal tillage and herbicide applications are necessary to ensure each system works to its full potential.…”
Section: Challenges Associated With Pgcmentioning
confidence: 99%